2022
DOI: 10.1128/spectrum.00345-22
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Hepatitis C Virus (HCV) Core Antigen Assay in the Diagnosis of Recently Acquired HCV Infection among High-Risk Populations

Abstract: The HCV core antigen assay has a high specificity of 99.4% and negative predictive value of 99.5% but a lower sensitivity of 87.1% and positive predictive value of 85.7% in the diagnosis of recently acquired HCV infection in high-risk populations. Our findings are informative for many countries confronted with limited resources to timely identify acute HCV infections and provide effective direct-acting antivirals to halt onward transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…The risk of bias was high in three articles (4%) for the patient selection domain, 40,86,99 seven studies (9.3%) for the index test domain, 30,66,68,75,82,83,96 and five studies (6.7%) for the flow and timing. 56,66,67,79,88 A similar trend was reported for concern regarding the applicability, where most studies (n = 61, 81.3%) reported low concerns. Moreover, all studies had low concerns regarding the applicability of the reference standard domain.…”
Section: Risk Of Bias Assessmentsupporting
confidence: 67%
See 1 more Smart Citation
“…The risk of bias was high in three articles (4%) for the patient selection domain, 40,86,99 seven studies (9.3%) for the index test domain, 30,66,68,75,82,83,96 and five studies (6.7%) for the flow and timing. 56,66,67,79,88 A similar trend was reported for concern regarding the applicability, where most studies (n = 61, 81.3%) reported low concerns. Moreover, all studies had low concerns regarding the applicability of the reference standard domain.…”
Section: Risk Of Bias Assessmentsupporting
confidence: 67%
“…Twenty‐one studies (28%) were found to have an overall low risk of bias. The risk of bias was high in three articles (4%) for the patient selection domain, 40,86,99 seven studies (9.3%) for the index test domain, 30,66,68,75,82,83,96 and five studies (6.7%) for the flow and timing 56,66,67,79,88 . A similar trend was reported for concern regarding the applicability, where most studies ( n = 61, 81.3%) reported low concerns.…”
Section: Resultsmentioning
confidence: 53%
“…65 Because of the possibility of reinfection in PWID after DAA treatment, testing for HCV reinfection at least annually and following any alanine aminotransferase elevation in PWID with SVR is recommended. 38 Posttreatment surveillance for HCV reinfection can be performed using pooled HCV RNA testing or HCV core antigen, 66,67 and retreatment should be offered in PWID with HCV reinfection to avoid continued transmission. Therefore, the combination of harm reduction services, treatment as prevention and regular posttreatment HCV surveillance is critical to substantially reduce HCV transmission and prevalence in PWID.…”
Section: Reinfection and Preventionmentioning
confidence: 99%
“…It is estimated that approximately 71 million individuals worldwide are living with chronic HCV infection, with an annual increase of 1.75 million new HCV infections 1,2 . Currently, HCV infection occurs predominantly in high‐risk populations, such as people who inject drugs (PWID), men who have sex with men (MSM), and human immunodeficiency virus (HIV)‐infected people 3–5 . The modeling demonstrated that the high‐risk populations, which represents only 7% of the population, accounts for 94% of all HCV infections 6 .…”
Section: Introductionmentioning
confidence: 99%
“…who have sex with men (MSM), and human immunodeficiency virus (HIV)-infected people. [3][4][5] The modeling demonstrated that the highrisk populations, which represents only 7% of the population, accounts for 94% of all HCV infections. 6 Although the advent of all-oral, highly effective direct-acting antiviral drugs that can cure HCV infection has made HCV infection a curable disease.…”
mentioning
confidence: 99%